On body, soul, and popular culture: A study of the perception of plague by muslim and coptic communities in Mamluk Egypt - Maslouh, Mohamed S. (AUC Knowledge Fountain, 2013)
This thesis studies the Muslim and Coptic medical, theological, and philosophical perceptions of plague in Mamluk Egypt (1250-1517). It also details the responses to mass death caused by plagues in both popular culture and mainstream scholarly works. This is carried out by illustrating the various medical, and theological parameters which influenced the different understandings of plague. Attention will be given to the diversity of the medical traditions which coexisted and, sometimes, overlapped in medieval Egypt. This reveals the inadequacy of the convenient classifications and distinctions between the different medical traditions, which have been previously employed to explain plague in medieval Egypt. Also, this thesis will explore the communal reactions of the Coptic minority in Egypt to plague in contrast to the prevalent discourse which ignores non- Muslims in medieval Islamic states and societies. It also discusses the philosophical questions that have been raised in the time of plague concerning fatalism, salvation, and divine punishment. Finally, it explores the perception of plague in popular culture in Mamluk Egypt, and reexamines the previous studies on plague which debated its influence on inter-communal social relations, by asking if the increased hostility to religious minorities was a result of the prevalence of plague.